Growth of coffee seedlings recently planted: effect of phosphorus sources and doses - Carmo, Davi Lopes; Takahashi, Heitor Yuji Uzuelle; Silva, Carlos Alberto; Gontíjo, Paulo Tácito (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the influence of different P sources and doses in the dynamics of P availability in soil contained in pots and on their impact on nutrition, P accumulation and biomass production in coffee recently planted. Treatments consisted of combinations of sources (organomineral fertilizer, superphosphate, rock phosphate, rock phosphate+filter cake and termalphosphate) and doses (200 and 400 mg kg-1) of P, and the control as in additional treatment (no P addition). It was evaluated the pH, Ca2+, Mg2+, P (Mehlich-1), CEC at pH 7, base saturation and soil organic matter, the accumulation of P and other nutrients in shoots and dry weight of shoot, root dry weight and total dry mass of coffee seedlings planted cultived in greenhouse conditions. The use of different sources of P imply significant changes in the degree of fertility of the soil, so that the dose of thermophosphate P need to be accurately calculated, since it causes exaggerated increases in pH and Ca2+ and Mg2+ in soil. The highest yields of dry matter were obtained when P was furnished as organomineral and phosphate+filter cake fertilizers, but the effect of these sources on the initial growth of the coffee plants depends on the dose applied. The use of organomineral fertilizer increased the accumulation of macro and micronutrients, in higher contents than those noted for most other phosphorus sources tested.